Choroidal Thickness and Urinary Albumin Excretion in Type 2 Diabetic Patients without Retinopathy - Cláudia Oliveira-Ferreira; Mariana Leuzinger-Dias; João Tavares-Ferreira; F. Falcão-Reis; Amândio Rocha-Sousa (Journal of Ophthalmology)
The role of retinal vasculature’s dysfunction in the physiopathology of Diabetic Retinopathy (DR) has been extensively described. Recently, the existence of a diabetic choroidal vasculopathy has been proposed. The purpose of this study was to compare choroidal thickness (CT) in nondiabetic patients and in type 2 diabetic patients without retinopathy, using EDI SD-OCT. Additionally, considering the diabetic patient group, compare CT in patients with and without microalbuminuria. This retrospective study selected patients sent from primary health-care centers as part of the national screening of diabetic retinopathy. Inclusion criteria were diagnosis of type 2 diabetes mellitus, absence of diabetic retinopathy, and a 24 hours urinary albumin measurement in the last 3 months at the primary health-care center. Nondiabetic patients were selected from a database in the ophthalmology department, and only healthy patients were included. At the screening visit, all patients performed a complete ophthalmologic examination by the same examiner. All eyes were examined with SD- OCT, and all scans were performed in the EDI mode. Measurements were made at three points: subfoveal, 1500 μm temporally and nasally to the foveal center. We included 110 eyes of 110 diabetic patients without diabetic retinopathy and 30 eyes of 30 healthy controls. Mean subfoveal CT was greater in diabetic patients without retinopathy (with normoalbuminuria or microalbuminuria) when compared with nondiabetic patients (p<0.05). In diabetic patients without retinopathy, the subfoveal and temporal choroid was thicker among patients with microalbuminuria when compared with those of normoalbuminuric patients (p<0.05). The subfoveal and temporal choroid was thicker among diabetic patients with microalbuminuria compared with nondiabetic patients. (p<0.05). This study suggests that choroidal changes are present in type 2 diabetic patients even before the clinical development of retinopathy.